Ferroptosis: a novel pathogenesis and therapeutic strategies for Parkinson disease: A review - Jiao, Di; Yang, Yang; Wang, Kejing; Wang, Yaomei (Medicine (Baltimore), 2025)
Parkinson disease (PD) is the second most common neurodegenerative disease, and its incidence is climbing every year, but there is still a lack of effective clinical treatments. In recent years, many studies have shown that ferroptosis plays a key role in the progression of PD. Most importantly, many cellular and animal studies and clinical trials have shown that episodes of PD can be alleviated by inhibiting the ferroptosis process, such as utilizing inhibitors, chelating agents, and others. Here, we review the role of ferroptosis, a new form of cell death, in the pathogenesis of PD, and summarize the therapeutic strategies for targeting ferroptosis in PD, hoping to provide new thinking for the study of PD pathogenesis and the development of therapeutic strategies.